Long-distance seed and pollen dispersal inferred from spatial genetic structure in the very low-density rainforest tree, Baillonella toxisperma Pierre, in Central Africa - (:unkn) unknown (My University, 2010)
We analysed the spatial distribution of genetic diversity to infer gene flow for Baillonella toxisperma Pierre (Moabi), a threatened entomophilous pollinated and animal-dispersed Central African tree, with typically low density (5-7 adults trees/km(2)). Fifteen nuclear and three universal chloroplast microsatellites markers were used to type 247 individuals localized in three contiguous areas with differing past logging intensity. These three areas were within a natural forest block of approximately 2886 km(2) in Gabon. Expected heterozygosity and chloroplast diversity were He-nuc = 0.570 and H-cp = 0.761, respectively. F-IS was only significant in one area (F-IS = 0.076, P < 0.01) and could be attributed to selfing. For nuclear loci, Bayesian clustering did not detect discrete gene pools within and between the three areas and global differentiation (F-STnuc = 0.007, P > 0.05) was not significant, suggesting that they are one population. At the level of the whole forest, both nuclear and chloroplast markers revealed a weak correlation between genetic relatedness and spatial distance between individuals: Sp(nuc) = 0.003 and Sp(cp) = 0.015, respectively. The extent of gene flow (sigma) was partitioned into global gene flow (sigma(g)) from 6.6 to 9.9 km, seed dispersal (sigma(s)) from 4.0 to 6.3 km and pollen dispersal (sigma(p)) from 9.8 to 10.8 km. These uncommonly high dispersal distances indicate that low-density canopy trees in African rainforests could be connected by extensive gene flow, although, given the current threats facing many seed disperser species in Central Africa, this may no longer be the case.
Keywords: African Research